NUCLEAR SECURITY IN THE BRAZILIAN REALITY - RODRIGO CARNEIRO CURZIO; JOAO CLAUDIO BATISTA FIEL; BRUNO DA SILVA MOURA; WALINTON EVANGELISTA DE SOUSA; LUAN JARDIM BONFIM (Brazilian Journal of Radiation Sciences, 2021)
This paper presents a study on the implementation of nuclear security’s knowledge in the brazilian reality, sharing the promotion of nuclear security education, aligned to guidelines and orientations of the IAEA, and covering fields such as The Regulatory Area and The Non- Regulatory Area. The study takes into account the acts of terrorism that indicate the use or threat of use of radioactive material, radiological weapons or even nuclear weapons, including local attacks where such materials are present. The Nuclear Security planning in a country includes everything. From planning a safety project from a core of a nuclear reactor to planning a gym's safety. It also includes physical security plan, safeguards plan, information security, the society's alert about any risk and actions to prevent and detect the different types of threats, such as the risk of sabotage, illegal transfer of radioactive material, among others.